You say it, we say it, but how do we use it? Communities of practice: A critical analysis. Issue 3 (18th December 2019) - McGrath, Cormac; Liljedahl, Matilda; Palmgren, Per J.
Abstract: Objectives: As educational theories are increasingly used in medical education research there are concerns over how these theories are used, how well they are presented and what the authors intend. Communities of practice (CoP) is one example of an often‐used theory and conceptual framework. This paper presents a critical analysis of how CoP theory is used in medical education research. Methods: A critical literature analysis was undertaken of articles published between 1998 and 2018 in eight internationally recognised medical education journals. From a total of 541 articles, 80 articles met the inclusion criteria and were analysed and mapped according to various patterns of use. Results: We discerned five categories of use, two misleading and cosmetic, off target and cosmeticising, and three functional, framing, lensing and transferring . A considerable number of articles either misrepresented the point of communities of practice or used it in a cosmetic fashion. The remainder used the theory to frame an ongoing study in relation to other work, as a lens through which to design the study and collect or analyse data, or as a way of discussing or demonstrating the transferability of the findings. Conclusions: We conclude that almost half of the reviewed articles did not offer a functional and rigorous definition of what is meant by CoP; instead, they used it in a potentially misleading or cosmetic manner. This study therefore calls on editors, reviewers and authors alike to increase clarity and quality in the application of CoP theory in medical education. Abstract : McGrath et al. use Communities of Practice literature to analyze how theory is used in health professional education. Their findings? Often in a predominantly cosmetic way, requiring more critical thought about how to advance our research strategies.